Pengembangan Sistem Informasi Perusahaan Konveksi dan Sablon Berbasis Website Menggunakan Metode Waterfall - Raja Sabaruddin; Mely Juniarti; Ardiyansyah Ardiyansyah; Wahyu Nugraha (LPPM Universitas Bina Sarana Informatika, 2020)
CV. Three Abdoel is a company engaged in convection and screen printing that accepts orders such as screen printing t-shirts, vests, hats, totebags, and goodiebags, as well as uniforms and sportswear clothing which are ordered from schools, individuals, government agencies, educational institutions, business entities such as cafes , restaurants, sap companies, palm oil, banks and others. In ordering activities customers come directly to the company to place an order. This is certainly not effective for costomers who are far away from the company, as well as the process of recording after ordering or reporting from the results of orders that are less effective because they still use handwriting and the absence of a specific book for recording. This can lead to the slow search process of previous data, the error rate in inputting and data manipulation is very large. For this reason, the author made the final assignment with the theme of ordering convection and screen printing entitled Ordering Information System for Convection and Screen Printing on CV. Three Abdoel Kubu Raya Web Based, this information system is expected to be a solution for companies in service to customers, increase company revenue and improve the process of recording orders or reports from the results of orders that use handwriting into a computerized system so that it will be more effective and efficient.